Determination of the effective radiation dose for mutation breeding in purple carrot (Daucus carota L.) and possible variations formed - Yarar, Gülistan; Kocak, Metin; Denli, Nihal; Cavagnaro, Pablo; Yildiz, Mehtap (Springer, 2021)
Background: Plant breeding allows altering the genetic structure of plants to meet human needs. The use of radiation technology for inducing mutations and -thereby- new phenotypic variants has become increasingly common as a tool for developing new crops. The aim of this study was to determine the effective gamma irradiation dose for inducing mutations in purple carrot. Methods and results: Increasing gamma radiation doses [0, 50, 100, 200, 300, 400, 500, and 600 Gy] were applied to purple carrot seeds. The irradiated seeds were sown in pots and the emergence and survival rates of the seedlings were analyzed. Considering plant emergence (%) as a response variable, the LD50 dose was 387.5 Gy. Analysis of root length, root width (shoulder diameter) and plant height in control (0 Gy) and irradiated plants (50–600 Gy) revealed an inverse association between these morphological traits and radiation dose. SRAP and ISSR markers were used to identify DNA polymorphisms in irradiated and control plants. The range of amplicons per primer set revealed by ISSR and SRAP markers was 4–10 and 2–13, respectively. In the ISSR analysis of the irradiated carrots (for the 8 doses used), we obtained range values for the average Nei’s gene diversity, Shannon’s information index, and polymorphism information content (PIC) of 0.13–0.25, 0.20–0.35, and 1.39–1.67, respectively, whereas in the SRAP analysis, the range values for these parameters were 0.15–0.25, 0.23–0.37, and 0.43–0.58, respectively. Cluster analysis revealed three main groups; (a) non-irradiated (control) plants, (b) plants from the 600 Gy dose, and (c) a third group with two subgroups: one with individuals from the lowest irradiation doses (50–200 Gy) and a second group with individuals from the highest irradiation doses (300–500 Gy). Conclusions: This is the first report on determining effective mutagen doses and genetic characterization of induced mutagenesis via gamma irradiation in purple carrot. ISSR and SRAP markers were successful in detecting variations among different levels of mutagen doses.